MANAJEMEN PENGELOLAAN CYBER PUBLIC RELATIONS DALAM MEWUJUDKAN GOOD GOVERNANCE PEMERINTAH KOTA PAYAKUMBUH - Erliansyah, Beni; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Payakumbuh city is one of the that is in the province of West Sumatra who also service is realize good governance in his reign. Any one principle in the concept of good governance namely freedom of information. Public relations is bridge in the delivery of information from the government to community. In any activity public relations need is done a the management of whether at a job that is conventional or have used media based the internet. The purpose of this research is to see how the process of planning , the implementation of up to the stage evaluation of programs and activities cyber technologies public relations which was carried out by city payakumbuh public relations .This study using methods the qualitative study .The study is done at the office of public relations agency of communication and informatic payakumbuh city , the province of west sumatera .The selection of informants done with purposive technique .Data collection techniques used during carry out research is by means of observation , interviews and documentation .While examination technique the validity of the data researchers used was a long of the participation, triangulation and sufficiency reference.The research results show that public relations using three its stages on the process of the management of cyber public relations namely the planning stages , the implementation of the , and evaluation .At the planning public relations do planning related planning activity management cyber public relations , planning people , planning time and planning media .In the implementation stage public relations do some main activities which were management process of information , election process media , the process of monitoring and communication , and the last was the role of related parties activities cyber public relations .At the evaluation public relations doing a variety of things that is evaluation target targets cyber public relations , time evaluation , and also evaluating people.Keywords: management, cyber public relations, public relations, good governance